2020
DOI: 10.1080/15548627.2020.1827780
|View full text |Cite
|
Sign up to set email alerts
|

ATF4 links ER stress with reticulophagy in glioblastoma cells

Abstract: Selective degradation of the endoplasmic reticulum (ER; reticulophagy) is a type of autophagy involved in the removal of ER fragments. So far, amino acid starvation as well as ER stress have been described as inducers of reticulophagy, which in turn restores cellular energy levels and ER homeostasis. Here, we explored the autophagy-inducing mechanisms that underlie the autophagic cell death (ACD)-triggering compound loperamide (LOP) in glioblastoma cells. Interestingly, LOP triggers upregulation of the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 64 publications
(134 reference statements)
0
64
0
Order By: Relevance
“…3A and 3F), indicating that the exposure of AECIIs to 95 % oxygen increased the expression of CHOP, a major pro-apoptotic transcription factor induced by ER stress. PERK and ATF6 were ERS sensors, ATF4 were their downstream-activated proteins that activated CHOP expression according to the previously reported mechanism [21][22][23]. As shown in Fig.…”
Section: Effects Of Hyperoxia On Grp-78 Chop and Ers Sensors Expressionmentioning
confidence: 66%
“…3A and 3F), indicating that the exposure of AECIIs to 95 % oxygen increased the expression of CHOP, a major pro-apoptotic transcription factor induced by ER stress. PERK and ATF6 were ERS sensors, ATF4 were their downstream-activated proteins that activated CHOP expression according to the previously reported mechanism [21][22][23]. As shown in Fig.…”
Section: Effects Of Hyperoxia On Grp-78 Chop and Ers Sensors Expressionmentioning
confidence: 66%
“…The development of drugs and therapeutic methods by targeting ER-phagy to treat related diseases is an emerging research field at present. For example, it has been reported that loperamide can induce the expression of Cyclic amp-dependent transcription factor ATF-4 (ATF4) in glioblastoma cells [ 138 ]. With the transcriptional activation by ATF4, FAM134B, and TEX264 expression is enhanced [ 138 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that loperamide can induce the expression of Cyclic amp-dependent transcription factor ATF-4 (ATF4) in glioblastoma cells [ 138 ]. With the transcriptional activation by ATF4, FAM134B, and TEX264 expression is enhanced [ 138 ]. Subsequently, excessive ER-phagy is induced and autophagic cell death of cancer cells is triggered [ 138 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, another study in GB cells demonstrated that ATF4 played a key role to induce autophagic cell death via reticulophagy (i.e. the selective degradation of the endoplasmic reticulum) in response to loperamide treatment and in this context activation of ATF4 was suggested to be beneficial for tumor therapy 38 . These studies highlight the ambiguous character of the ATF4 mediated stress response depending on the experimental context.…”
Section: Discussionmentioning
confidence: 99%